2019
DOI: 10.1038/s41419-019-1708-9
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential ion-channel subfamily V member 4: a potential target for cancer treatment

Abstract: The transient receptor potential ion-channel superfamily consists of nonselective cation channels located mostly on the plasma membranes of numerous animal cell types, which are closely related to sensory information transmission (e.g., vision, pain, and temperature perception), as well as regulation of intracellular Ca 2+ balance and physiological activities of growth and development. Transient receptor potential ion channel subfamily V (TRPV) is one of the largest and most diverse subfamilies, including TRPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 203 publications
(128 reference statements)
1
39
0
Order By: Relevance
“…The pore loop is between segments 5 and 6 and both the C-and N-termini are located within the cytoplasm (31). The channel contains six ankyrin repeats and the phospholipid, phosphatidylinositol 4,5-bisphosphate (PIP2), can bind to this site inhibiting the channel (32). Similar to TRPV1, TRPV4 is expressed on a variety of cells such as neurons, leukocytes (33), T cells (34), and macrophages (35).…”
Section: Trpv4mentioning
confidence: 99%
“…The pore loop is between segments 5 and 6 and both the C-and N-termini are located within the cytoplasm (31). The channel contains six ankyrin repeats and the phospholipid, phosphatidylinositol 4,5-bisphosphate (PIP2), can bind to this site inhibiting the channel (32). Similar to TRPV1, TRPV4 is expressed on a variety of cells such as neurons, leukocytes (33), T cells (34), and macrophages (35).…”
Section: Trpv4mentioning
confidence: 99%
“…Similarly, elevated levels of TRPV4 in breast, gastric, ovarian, and colon cancers correlates with increased cancer cell proliferation, invasion, and poor patient survival [214][215][216]. On the contrary, the expression level of TRPV4 is significantly reduced in advanced endothelial and skin cancers [211,217], suggesting that TRPV4 exhibits both oncogenic or tumour suppressor effects depend on the cancer type [218]. Moreover, TRPV5 was found downregulated in lung [219] and renal [220] tumours, and its reduced expression correlates with poor overall survival and short relapse-free survival of lung cancer patients [219].…”
Section: Trpvmentioning
confidence: 99%
“…Nowadays, there is an increasing interest in ion channels, especially the mechanosensitive ion channels, as potential drug targets in many types of cancers. [1][2][3][4] Transient receptor potential vanilloid 4 (TRPV4) is the vanilloid subfamily of the TRP channels, which is involved in mechanotransduction processes like volume regulation and osmosensing. 4 Mechanical stress is a critical mediator of cancer progression and mechanosensitive ion channels are functionally up-regulated in cancers that depend on Ca 2+ signaling.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Transient receptor potential vanilloid 4 (TRPV4) is the vanilloid subfamily of the TRP channels, which is involved in mechanotransduction processes like volume regulation and osmosensing. 4 Mechanical stress is a critical mediator of cancer progression and mechanosensitive ion channels are functionally up-regulated in cancers that depend on Ca 2+ signaling. 3,5,6 Several studies demonstrated that TRPV4 was overexpressed in different types of cancers, including human colon cancer, breast cancer, and hepatocellular carcinoma, and was involved in cancer cell proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation